Short sprints are more related to on-ice speed than other traditional off-ice power performance tests - Hamil, J.; Triplett, A.; Vorkapich, M.; Pivarnik, J. (The Journal of Strength and Conditioning Research, 2021)
Ice hockey is a high-intensity sport and players must produce substantial power and reach high skating velocities during competition. Game analyses demonstrate elite players perform 19 sprints averaging 26 m and 94 high-intensity skating bouts averaging 15-16 m during competition (Lignell et al. 2018). Consequently, power performance evaluation is critical to identify player talent for hockey professionals. Off-ice performance tests are used to evaluate ice hockey players' power, but little is known about their relationships to on-ice tests. Purpose: To compare power performance measures obtained during off- and on-ice performance tests in collegiate ice hockey players. Methods: Twenty-three male, collegiate ice hockey players (age = 18-24 years, ht = 1.82 ± 0.05 m, wt = 84.9 ± 4.74 kg) were assessed during the first transition phase of the 2019-2020 season. Off-ice performance tests included 5- and 10-yard running sprints, vertical jump (VJ), and the 30-second Wingate cycle test. The on-ice performance test was the repeat shift ability (RSA) test (Peterson et al. 2014). All tests were performed on separate days to maximize performance and rest between evaluations. Five- and 10-yard sprints were measured for time (sec) using timing gates. Sprints were performed on an indoor turf surface and players were given 2 opportunities for each distance with ~3 minutes rest. The VJ test was used to measure jump height using a VJ tester. Players were given opportunity to retest until failure to improve on their previous jump height. The Wingate was used to assess peak power on a Monark cycle ergometer. Results were compared to the time it took to go through the first gate (G1) of the electronically timed RSA. Spearman correlations were used to assess relationships between results from each off-ice test with the on-ice test. Results: Sprint times for the 5- and 10-yard tests averaged 1.06 ± 0.06 and 1.79 ± 0.06 seconds respectively. VJ heights were 30.3 ± 2.5 in and Wingate peak power measured 997 ± 134 W. Fastest G1 skate times averaged 9.55 ± 0.43 sec. The 5- and 10-yard sprints were both significantly related to the G1 time (r = 0.416, p < 0.05; r = 0.436, p < 0.05). There were no significant relationships between VJ height (r = -0.366, ns) or Wingate peak power (r = 0.003, ns) and G1 times. Conclusions: Moderate correlations between the 5- and 10-yard sprint times and the G1 times were not surprising given both tests rely on similar energy systems and are largely influenced by players' ability to develop speed. Based on previous literature, we expect VJ and Wingate are valuable for identifying player performance potential, but these tests did not relate to the on-ice performance test. Lack of relationship between these off-ice tests and the on-ice test however should not fully discredit the use of these off-ice tests for assessing player performance as previous literature suggests off-ice tests are predictive of performance during competition. Practical Applications: When selecting an off-ice performance test to evaluate ability to develop power, on or off the ice, the 5- and 10-yard running sprints may be most applicable. Bipedal, weight bearing requirements for this test are most similar to skating locomotion compared to other tests evaluated. These tests may provide insight into players' ability to develop speed, which is necessary for achieving position or finding space during competition -elements critical to hockey strategy.